Proteomic analysis of the influence of Cu(2+) on the crystal protein production of Bacillus thuringiensis X022 - Liu, Xuemei (Microb Cell Fact, 2015)
BACKGROUND: Bacillus thuringiensis X022, a novel strain isolated from soil in China, produces diamond-shaped parasporal crystals. Specific mineral nutrients, such as Mg, Cu, and Mn, influence insecticidal crystal proteins (ICP) expression and the effects of these elements vary significantly. However, the molecular mechanisms of the effects caused by mineral elements have yet to be reported. RESULTS: The ICP are mainly composed of Cry1Ca, Cry1Ac, and Cry1Da, which have molecular weights of about 130 kDa. ICP production was most efficient when Cu(2+) was added at concentrations ranging from 10(−6) to 10(−4) mol/L at an initial pH of 8.0. Addition of Cu(2+) also evidently increased the toxicity of fermentation broth to Spodoptera exigua and Helicoverpa armigera. After analyzing changes in proteome and fermentation parameters caused by Cu(2+) addition, we propose that Cu(2+) increases PhaR expression and consequently changes the carbon flow. More carbon sources was used to produce intracellular poly-β-hydroxybutyrate (PHB). Increases in PHB as a storage material bring about increases of ICP production. CONCLUSIONS: Bacillus thuringiensis X022 mainly expresses Cry1Ca, Cry1Ac, and Cry1Da. Cu(2+) increases the expression of Cry1Da, Cry1Ca, and also enhances the toxicity of fermentation broth to S. exigua and H. armigera. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-015-0339-9) contains supplementary material, which is available to authorized users.